Financing in the alternative securities market: Economic and financial impact on SMEs - Salazar-Rebaza, Carola (2022)
In Latin America, SMEs have difficulty accessing sources of financing that allow them to obtain more significant growth and strengthen their economic activity. Therefore, this paper aims to determine the impact of financing in the alternative securities market (MAV) on the economic and financial situation of Peruvian SMEs during 2017–2020. The methodology used in this study is a quantitative approach, descriptive, non-experimental design, and longitudinal measurement. In addition, a documentary analysis technique is employed. The population included 17 SMEs financed in the MAV; the paper considers the financial statements of 6 companies in the last 4 years as a sample. The results obtained show that SMEs financed through the MAV are of different categories and economic activities. Likewise, there is a predisposition of these in the issuance and placement of short-term instruments, determining a favorable economic and financial situation through the analysis of financial indicators, with sustainable profitability growth and an acceptable liquidity and solvency situation. The conclusion is that financing in the alternative securities market has contributed to the improvement of SMEs’ economic and financial state, allowing for sustainable growth and opportunities to diversify their operations.